2022
DOI: 10.3390/s22166169
|View full text |Cite
|
Sign up to set email alerts
|

Cycling through 360° Virtual Reality Tourism for Senior Citizens: Empirical Analysis of an Assistive Technology

Abstract: In recent years, there has been a renewed interest in using virtual reality (VR) to (re)create different scenarios and environments with interactive and immersive experiences. Although VR has been popular in the tourism sector to reconfigure tourists’ relationships with places and overcome mobility restrictions, its usage in senior cyclotourism has been understudied. VR is suggested to positively impact tourism promotion, cycling simulation, and active and healthy ageing due to physical and mental rehabilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…In addition, VR has shown that interactive training with visual feedback can outperform traditional physical training in improving functional mobility and balance in older adults. The multiple feedback and engaging nature of VR training could make it more effective and motivating, highlighting its distinct advantages in geriatric care and rehabilitation ( 18 , 19 ).…”
Section: Ready Set Vr! the Senior Sprint Into A Healthier Digital Fro...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, VR has shown that interactive training with visual feedback can outperform traditional physical training in improving functional mobility and balance in older adults. The multiple feedback and engaging nature of VR training could make it more effective and motivating, highlighting its distinct advantages in geriatric care and rehabilitation ( 18 , 19 ).…”
Section: Ready Set Vr! the Senior Sprint Into A Healthier Digital Fro...mentioning
confidence: 99%
“…Undoubtedly, VR offers therapeutic opportunities that allow the aging population to engage in activities they previously avoided. The innovative integration of virtual natural environments clearly increases older adults’ motivation to exercise, as evidenced by their increased participation in virtual cycling, for example ( 19 ). This technological alchemy captures the rejuvenating essence of nature and makes it accessible even to people with pronounced physical limitations ( 28 ).…”
Section: Putting the “Real” In Virtual: Inclusion Accessibility And M...mentioning
confidence: 99%
“…In this context, we propose, develop, and validate an architecture for a sensory-experiential marketing system based on 360° VR technology. VR employs virtual environments that allow users to move freely within the virtual space, while 360° VR offers spherical/panoramic experiences [ 3 ]. 360° immersive video has gained popularity in contemporary applications due to several studies indicating that it enhances perception.…”
Section: Introductionmentioning
confidence: 99%
“…VR applications offer numerous benefits, including use among older adults [ 2 , 5 , 6 ]. VR applications are intended to specifically promote the competencies of the older adults and to help them achieve more independence in old age [ 7 ]. Figure 1 illustrates various application fields in VR for older adults, along with 2 existing exemplary scenarios.…”
Section: Introductionmentioning
confidence: 99%